Investigation of the DGS-CDRA design with the aperture coupling technique for wide band application - Che Abdullah, S.M. (Springer Verlag, 2017)
In this paper, a design of wideband antenna by tuning the aperture slot parameters and using two dielectric pellets is investigated and discussed. The performance of the resonant frequencies, impedance bandwidth and radiation pattern of the DGS-CDRA (Defected Ground Structure Cylindrical Dielectric Resonator Antenna) are analyzed. The design achieved a wideband impedance bandwidth of 4.0 GHz (50.74 ) by using two slots aperture and thick substrate. Two dielectric pellets with the same type and size are coupled to a microstrip line through two rectangular slots. The slots positions are tuned along (below) microstrip line to a position where impedance bandwidth from both dielectric pellets are merged and form a wide impedance bandwidth. Subsequently, performance of the antenna is being analyzed based on the simulation results of return loss and radiation pattern. The design is fabricated and the measurement results of impedance bandwidth are compared with the simulation results. © Springer Science+Business Media Singapore 2017.